Analiza finansowa ex ante a modelowanie wartości przedsiębiorstwa - Krysiak, Zbigniew (Application of Company Value Modeling in Financial Analysis ex ante, 2006)
Dynamic changes in economic environment require today a modern approach in financial analysis. Modeling of the company value based on Monte Carlo simulation and option model enables to facilitate the tool which anticipates probability distribution together with probability of default Financial analysis should answer the questions about the highest speed a company could develop without loosing liquidity. The approach presented in the above paper tries to answer the question mentioned above. Different studies performed by the author indicate that the proposed seems to be a promising tool for financial analysis ex ante
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 369-382